Hubungan Antara Kepatuhan Terapi Antiretroviral terhadap Terjadinya Kondisi Underweight, Lingkar Betis, Handgrip Strength, dan Skinfold Triceps pada Pasien HIV/AIDS di RSSA Malang - Budiarti, Niniek; Kurniawan, Fitto; Soenarti, Sri (Jurnal Klinik dan Riset Kesehatan, 2024)
Background: Human Immunodeficiency Virus or commonly known as HIV is a virus that infects CD4 cells thereby impaired the human immune system. The number of new HIV cases in Indonesia in 2019 was reported to have reached 50,282 cases and tends to increase from year to year. What often happens in people with HIV/AIDS (PLWHA) tends to experience weight loss accompanied by opportunistic infections that do not occur in normal people. Adherence to therapy is the main factor that must be emphasized by PLWHA in order to achieve treatment success. However, ARV therapy adherence rates are reported to be <80%. This number can be a predictor of therapy failure. One indicator of the success of therapy is when there is clinical improvement in the patient's condition, such as no opportunistic infections or weight gain. Aim: The aim of this study was to determine whether there is a relationship between adherence to antiretroviral therapy and underweight conditions in HIV/AIDS patients. Methods: This study used a cross sectional design with an analytical observational nature and the research subjects were patients at RSSA Malang who visited from June to August 2023. Results: The results of the study showed that there was a significant relationship between adherence to taking ARVs and being underweight (p=0.018) and there was no significant relationship between adherence to taking ARVs with calf circumference, handgrip strength, and triceps skinfold. Conclusion: The conclusion of this study is that the more compliant the patient is with ARV therapy, the higher the increase in body mass index and the smaller the possibility of becoming underweight.